EVALUASI KEBISINGAN AKIBAT LALU LINTAS PADA JALAN TOL JAKARTA-TANGERANG - KADARSA, EDI
Noise Evaluation Caused by Traffic on Jakarta-Tangerang Toll Road, Kadarsa, E, 2002, Program Magister Teknik Sipil, Rekayasa Transportasi, Institut Teknologi Bandung. There are a lot of variables in the traffic which cause noise. The results of several studies done by experts show that there are several variables which are dominant in contributing to the traffic noise, which are the traffic flow, speed of vehicles, and percentage of heavy duty vehicles. The study was conducted on the Jakarta Â– Tangerang toll road, an out-of-town toll road, with structure of flexible pavement and is used by a lot of heavy duty vehicles. Noise variables which is researched is the traffic from Tangerang to Jakarta. Otherwise the traffic from Jakarta to Tangerang is supposed as background noise. There were three measurement location, namely : The 1 th location (IR1=2,7 m/km), the 2nd location (IRI=3,4 m-km), and The 3rd location (IRI= 2 m/km). Based on the on-site measurement, known the level of noise on three location, affect independent variables versus the level of noise, and mathematical relationship between the level of noise and independent vanables (the traffic flow, the average speed of vehicles, and the percentage of heavy duty vehicles). Mathematical relationship from the study at the site where instrument is placed 5 meters from the pavement edge is : Leq[dB(A)] = 25.734 + 5.819 Log Xl + 17.362 LogX2 + 2.333 Log X3 Otherwise Mathematical relationship from the study at the site where instrument is placed 13 meters from the pavement edge is : Leq[dB(A)] = 74.207 + 2.774 Log X3 At the site where the noise-measuring instrument is placed 5 meters from the pavement edge, all the free variables (traffic flow. average vehicle speed and the percentage of heavy duty vehicle) obviously affect the fluctuation of noise. However, at the site where the instrument is placed 13 meters from the pavement edge, only the variable of the percentage of heavy duty vehicle gives obvious impact on the production of noise. The problem was be caused instrument position farther than traffic noise, but nearer to village (background noise), therefore traffic noise was caught worse by instrument, but the noise traffic of nearest lane was caught better than other lane. On slow lane. almost along measurement time, heavy trucks and light trucks made convoy. The convoy was barrier for vehicles beside slow lane. Tice wind against noise propagation to instrument. The problem caused traffic noise which got handicap by heavy vehicles on slow lane get less.